Production method of double-sided roughened copper foil, double-sided roughened copper foil and production equipment
By using double-sided roughening copper foil in lithium metal batteries, the problem of lithium dendrites is solved, the safety and cycle stability of the battery are improved, and the volume energy density is improved.
Patent Information
- Application Number
- CN202311124063.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-04
AI Technical Summary
The double-sided light copper foil used in existing lithium-ion batteries and lithium metal batteries is prone to form lithium dendrites during charging and discharging, resulting in puncture and short circuit of the diaphragm, threatening the safety of the battery.
Additive-assisted electrochemical deposition technology is used to form undulating peak-like roughening structures on the double-sided light copper foil, and an anti-oxidation layer is formed on the surface of the copper foil through chromium-free passivation technology to form double-sided roughening copper foil.
Through the use of double-sided roughened copper foil, the formation and growth of lithium dendrites can be effectively suppressed, the safety and circulation stability of lithium metal batteries can be improved, and the volume energy density of the battery can be improved.
Smart Images

Figure CN119553320A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic circuit material processing, and in particular to a production method of a double-sided roughened copper foil, a double-sided roughened copper foil and production equipment. Background Art
[0002] Lithium-ion batteries have become the mainstream of electrochemical energy storage due to their small size, high energy density and strong customizability. They are widely used in power vehicles, consumer electronics and large-scale energy storage. In recent years, as the demand for energy density has become increasingly higher, the performance of conventional lithium-ion batteries with graphite as the negative electrode material has approached the theoretical limit. Lithium metal has the lowest electrochemical reaction potential and the lowest mass density. Lithium metal batteries with lithium metal as electrodes have become an important research direction for improving the energy density of lithium batteries.
[0003] Among them Figure 1 As shown in Figure 1, the structure of a lithium metal battery is mainly composed of copper foil, negative electrode material, separator, positive electrode material, aluminum foil and electrolyte. Copper foil, as the negative electrode current collector of a lithium metal battery, plays the role of current conduction and carrying lithium metal negative electrode material in a lithium metal battery.
[0004] Conventional lithium-ion batteries and lithium metal batteries mostly use double-sided smooth copper foil with relatively low roughness on both sides as the negative electrode current collector. It should be pointed out that double-sided smooth copper foil has the problem of lithium dendrites caused by random lithium deposition during the battery charging and discharging process. The formation of lithium dendrites may pierce the separator and cause direct contact between the positive and negative electrodes of the battery, thus forming a short circuit, which seriously threatens the safety of lithium-ion batteries and lithium metal batteries. Summary of the invention
[0005] In response to the above technical problems, the present invention provides a production method of double-sided roughened copper foil, double-sided roughened copper foil and production equipment, which are not only beneficial to improving the volume energy density of lithium metal batteries, but also beneficial to inhibiting the formation and growth of lithium dendrites to improve the safety of lithium metal batteries, and also improve the cycle stability of lithium metal batteries.
[0006] To achieve the above object, the present invention provides the following technical solution: a method for producing a double-sided roughened copper foil, characterized in that it comprises the following steps:
[0007] S1. Electrochemically depositing a single-sided roughened copper foil using additives. By introducing additives, the electrochemical deposition process of copper ions is regulated to form a single-sided roughened electrolytic copper foil with one side being flat and the other side having undulating peaks.
[0008] S2, electrochemically depositing a roughened structure on the smooth surface of the single-sided roughened copper foil; forming a roughened structure with undulating peaks on the smooth surface of the single-sided smooth copper foil through an additive-assisted electrochemical deposition process, thereby forming a double-sided roughened electrolytic copper foil;
[0009] S3. Anti-oxidation treatment is performed on both sides of the double-sided roughened copper foil. An oxide layer is deposited on the upper and lower surfaces of the double-sided roughened copper foil by pulse electrochemical deposition through chromium-free passivation technology to prevent oxidation and deterioration of the copper foil during use.
[0010] S4, drying the double-sided roughened copper foil; removing the residual moisture on the surface of the copper foil by passing the double-sided anti-oxidation treated copper foil through a blast oven;
[0011] S5. Finally, the double-sided roughened electrolytic copper foil is rolled up. The double-sided roughened copper foil that has completed the double-sided anti-oxidation treatment is rolled up into a roll by a rolling device under a certain tension, so as to facilitate the use in the downstream production process.
[0012] Furthermore, the same electrolyte is used in the electrochemical deposition of single-sided copper foil and the roughening of the surface, wherein the main components of the electrolyte include CuSO4, H2SO4, Cl - and leveling agents.
[0013] Furthermore, the leveling agent in the electrolysis and roughening electrolyte includes one or more of hydroxyethyl cellulose HEC, choline chloride, gelatin, and collagen, wherein the concentration of the leveling agent is between 5-20 mg / L.
[0014] Furthermore, the thickness of the double-sided roughened copper foil is between 6 and 10 μm, the roughness difference ΔRz between the two sides of the double-sided roughened copper foil is less than or equal to 1.0 μm, and the color difference ΔE between the upper and lower sides of the double-sided roughened copper foil is less than or equal to 2.0.
[0015] Furthermore, the anti-oxidation treatment liquid used for chromium-free passivation includes one or more of phytic acid (PA), benzotriazole (BTA), KH792 silane coupling agent, graphene oxide (GO), pyrrole (Py), aniline (ANI), and zinc sulfate (ZnSO4), wherein the concentration of the anti-oxidation treatment liquid is between 0.5-1.5 g / L.
[0016] Furthermore, the average current density during the pulse electrochemical deposition of the double-sided roughened copper foil anti-oxidation layer is 5-15A / m 2 The duty cycle is between 25-67% and the frequency is between 100-2000Hz.
[0017] A double-sided roughened copper foil is prepared according to the production method of the double-sided roughened copper foil.
[0018] Furthermore, the finished double-sided roughened copper foil has undulating mountain-like microscopic morphology on both sides, and the roughness Rz of the upper and lower surfaces is between 1.5-3.0 μm.
[0019] A production device for double-sided roughened copper foil, comprising the following equipment:
[0020] 1) Single-sided roughened copper foil electrochemical deposition device;
[0021] 2) Electrochemical deposition device for roughening the surface;
[0022] 3) Double-sided anti-oxidation electrochemical deposition device;
[0023] 4) Blast drying device;
[0024] 5) Double-sided roughened electrolytic copper foil winding device.
[0025] Furthermore, an auxiliary cathode is provided in the anti-oxidation treatment tank in the double-sided anti-oxidation electrochemical deposition device to remove copper ions brought into the copper foil surface from the treatment solution to ensure the effectiveness of the anti-oxidation treatment. The auxiliary cathode is made of a copper rod and the current is between 5-15A.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. In the present invention, a double-sided roughened electrolytic copper foil with excellent performance is produced by combining additive-assisted electrochemical deposition technology with chromium-free passivation surface treatment technology.
[0028] 2. In the present invention, compared with conventional double-sided smooth copper foil for lithium-ion batteries, the double-sided roughened electrolytic copper foil for lithium metal batteries produced by the present invention can effectively increase the loading amount of lithium metal per unit area, reduce the thickness of the lithium metal layer, and at the same time help to improve the volume energy density of the lithium metal battery.
[0029] 3. In the present invention, the double-sided roughened electrolytic copper foil is used to induce uniform deposition of lithium metal batteries during the charge and discharge process, which is beneficial to inhibit the formation and growth of lithium dendrites and improve the safety of lithium metal batteries.
[0030] 4. In the present invention, the contact area between lithium metal and the current collector is increased by using double-sided roughened electrolytic copper foil, which is beneficial to improving the binding force between lithium metal and copper foil, thereby improving the cycle stability of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.
[0032] In the attached picture:
[0033] Figure 1 Schematic diagram of the structure of the lithium metal battery of the present invention;
[0034] Figure 2 Schematic diagram of the effect of double-sided polishing and double-sided roughening of copper foil on lithium deposition in the present invention;
[0035] Figure 3 It is a schematic diagram of the structure of the double-sided roughened electrolytic copper foil production equipment of the present invention;
[0036] Figure 4 Schematic diagram of the cross-section SEM image of the double-sided roughened copper foil of Example 1 of the present invention;
[0037] Figure 5 Schematic diagram of SEM image of double-sided roughened copper foil of Example 1 of the present invention; wherein (a) is the upper surface; (b) is the lower surface;
[0038] Figure 6 This is a confocal laser profile cloud image of the double-sided roughened copper foil of Example 1 of the present invention, wherein (a) is the upper surface, and (b) is the lower surface image;
[0039] Numbers in the figure: 1. Copper foil; 2. Negative electrode material; 3. Separator; 4. Positive electrode material; 5. Aluminum foil. DETAILED DESCRIPTION
[0040] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0041] A method for producing a double-sided roughened copper foil comprises the following steps:
[0042] S1. Electrochemically depositing a single-sided roughened copper foil using additives. By introducing additives, the electrochemical deposition process of copper ions is regulated to form a single-sided roughened electrolytic copper foil with one side being flat and the other side having undulating peaks.
[0043] S2, electrochemically depositing a roughened structure on the smooth surface of the single-sided roughened copper foil; forming a roughened structure with undulating peaks on the smooth surface of the single-sided smooth copper foil through an additive-assisted electrochemical deposition process, thereby forming a double-sided roughened electrolytic copper foil;
[0044] The same electrolyte is used in the electrochemical deposition of single-sided copper foil and the roughening of the surface. The main components of the electrolyte include CuSO4, H2SO4, Cl - and a leveling agent; and the leveling agent in the electrolysis and roughening electrolyte includes one or more of hydroxyethyl cellulose HEC, choline chloride, gelatin, and collagen, wherein the concentration of the leveling agent is between 5-20 mg / L;
[0045] The thickness of the double-sided roughened copper foil is between 6 and 10 μm, the roughness difference ΔRz between the two sides of the double-sided roughened copper foil is less than or equal to 1.0 μm, and the color difference ΔE between the upper and lower sides of the double-sided roughened copper foil is less than or equal to 2.0;
[0046] S3. Anti-oxidation treatment is performed on both sides of the double-sided roughened copper foil. An oxide layer is deposited on the upper and lower surfaces of the double-sided roughened copper foil by pulse electrochemical deposition through chromium-free passivation technology to prevent oxidation and deterioration of the copper foil during use.
[0047] The anti-oxidation treatment liquid used for chromium-free passivation includes one or more of phytic acid (PA), benzotriazole (BTA), KH792 silane coupling agent, graphene oxide (GO), pyrrole (Py), aniline (ANI), and zinc sulfate (ZnSO4), wherein the concentration of the anti-oxidation treatment liquid is between 0.5-1.5 g / L; the average current density during the pulse electrochemical deposition of the anti-oxidation layer of the double-sided roughened copper foil is between 5-15 A / m 2 The duty cycle is between 25-67% and the frequency is between 100-2000Hz.
[0048] S4, drying the double-sided roughened copper foil; removing the residual moisture on the surface of the copper foil by passing the double-sided anti-oxidation treated copper foil through a blast oven;
[0049] S5. Finally, the double-sided roughened electrolytic copper foil is rolled up. The double-sided roughened copper foil that has completed the double-sided anti-oxidation treatment is rolled up into a roll by a rolling device under a certain tension, so as to facilitate the use in the downstream production process.
[0050] like Figure 2 As shown, a double-sided roughened copper foil is prepared in an electrolysis-roughening-passivation integrated machine according to the production method of the double-sided roughened copper foil, without the need for additional surface treatment. The finished double-sided roughened copper foil has undulating mountain-like microscopic morphologies on both sides, and the roughness Rz of the upper and lower surfaces is between 1.5-3.0 μm.
[0051] exist Figure 2 As shown in (a), conventional lithium-ion batteries and lithium metal batteries mostly use double-sided smooth copper foil with relatively low roughness on both sides as the negative electrode current collector. Double-sided smooth copper foil has the problem of random lithium deposition and lithium dendrites during the charge and discharge process of the battery. Compared with conventional double-sided smooth copper foil, Figure 2 The double-sided roughening developed by the present invention in (b) can induce the deposition of lithium during the charge and discharge process of the battery, thereby helping to suppress the disordered growth of lithium dendrites.
[0052] It can be seen that the double-sided roughened copper foil of the present invention can effectively increase the contact area between the electrode material and the current collector to improve the current transfer efficiency, and on the other hand, the valley area between adjacent peaks provides a buffer space for the growth of lithium dendrites, which is beneficial to inhibit the disordered growth of lithium dendrites.
[0053] like Figure 3 As shown, a production equipment for double-sided roughened copper foil includes the following equipment:
[0054] 1) Single-sided roughened copper foil electrochemical deposition device;
[0055] 2) Electrochemical deposition device for roughening the surface;
[0056] 3) Double-sided anti-oxidation electrochemical deposition device;
[0057] 4) Blast drying device;
[0058] 5) Double-sided roughened electrolytic copper foil winding device.
[0059] Among them, an auxiliary cathode is provided in the anti-oxidation treatment tank in the double-sided anti-oxidation electrochemical deposition device to remove the copper ions brought into the copper foil surface from the treatment liquid to ensure the effectiveness of the anti-oxidation treatment. The auxiliary cathode is made of copper rod and the current is between 5-15A.
[0060] Embodiment 1:
[0061] The present invention provides a production method of a double-sided roughened copper foil for a lithium metal battery, a double-sided roughened copper foil and a production device, the specific contents of which are as follows:
[0062] S1. Additive-assisted electrochemical deposition of single-sided roughened copper foil
[0063] In the S01 single-sided roughened copper foil electrochemical deposition device, copper sulfate and sulfuric acid are used as the main components of the electrolyte, and additives with a certain inhibitory effect are added to the electrolyte, and electrochemical deposition is carried out under the action of direct current. The parameters in the single-sided roughened copper foil electrochemical deposition process are as follows:
[0064] Cu 2+ Concentration: 80g / L
[0065] H2SO4 concentration: 200g / L
[0066] Collagen (Mw 2500-3500) concentration: 5mg / L
[0067] Cl - Concentration: 15ppm
[0068] Electrolyte temperature: 55°C
[0069] Electrolyte flow rate: 40m3 / h
[0070] Current density: 80A / dm 2
[0071] Cathode roller line speed: 5.0m / minS2, additive-assisted copper foil surface roughening treatment
[0072] The single-sided roughened electrolytic copper foil generated in the S01 single-sided roughened copper foil electrochemical deposition device is peeled off by a peeling roller and then runs to the S02 smooth surface roughened electrochemical deposition device to perform electrochemical roughening treatment on the smooth surface of the electrolytic copper foil. The specific parameters in the smooth surface electrochemical roughening process are as follows:
[0073] Cu 2+ Concentration: 80g / L
[0074] H2SO4 concentration: 200g / L
[0075] Collagen (Mw 2500-3500g / mol) concentration: 5mg / L
[0076] Cl - Concentration: 15ppm
[0077] Electrolyte temperature: 55°C
[0078] Electrolyte flow rate: 40m 3 / h
[0079] Current density: 80A / dm 2
[0080] Current density: 8kA / m 2
[0081] Running speed: 5.0m / minS3, double-sided roughened copper foil anti-oxidation treatment
[0082] The double-sided roughened copper foil generated by the S02 smooth surface roughening electrochemical deposition device is run into the S03 double-sided anti-oxidation electrochemical deposition device, and the surface of the double-sided roughened copper foil is subjected to anti-oxidation treatment under the pulse current provided by the pulse power supply. During the anti-oxidation treatment, a passivation layer is generated on the surface of the copper foil that isolates oxygen and water vapor in the air, thereby improving the anti-oxidation performance and processability of the copper foil during transportation, storage and downstream processing. The specific parameters during the anti-oxidation treatment of the double-sided roughened copper foil are as follows:
[0083] Graphene oxide concentration: 0.5g / L
[0084] Average current density: 10A / dm 2
[0085] Duty cycle: 33%
[0086] Frequency: 1000Hz
[0087] Auxiliary cathode current: 5AS4, blast drying and drying treatment
[0088] The double-sided roughened copper foil with an anti-oxidation layer formed on the surface after being treated by the S03 double-sided anti-oxidation electrochemical deposition device is run to the S04 blast drying treatment device to remove the residual moisture on the surface of the copper foil. The specific parameters of the blast drying treatment process are as follows:
[0089] Heating power: 10kW
[0090] Oven temperature: 150℃
[0091] Lower plate air blowing speed: 2.5m / s
[0092] Upper plate air blowing speed: 2.0m / s
[0093] Running speed: 5m / minS5, double-sided roughened copper foil winding
[0094] The double-sided roughened electrolytic copper foil treated by the S04 blast drying treatment device is run to the S05 double-sided roughened copper foil winding device, and the uneven edge surface density is cut off and then collected and rolled into a roll. The specific parameters of the double-sided roughened copper foil winding process are as follows:
[0095] Cutter diameter: 100mm
[0096] Cutting speed: 2.5m / min
[0097] Winding tension: 40kN
[0098] Winding speed: 5.0m / min
[0099] Air shaft pressure: 0.25MPa
[0100] Effect of the embodiment: The physical properties of the double-sided roughened copper foil produced by the parameters of this embodiment are as follows: copper foil thickness 8.0 μm, upper surface roughness Rz 1.91 μm, upper surface interface expansion area ratio Sdr 7.96%, lower surface roughness 2.05 μm, lower surface interface expansion area ratio Sdr 8.55%, and upper and lower surface color difference ΔE is 1.2.
[0101] Embodiment 2:
[0102] The difference between this comparative example and Example 1 is that the additive type and additive concentration in the copper foil electrochemical deposition process are adjusted: the collagen (Mw 2500-3500 g / mol) with a concentration of 5 mg / L in the electrolyte is replaced with hydroxyethyl cellulose HEC with a concentration of 20 mg / L.
[0103] Embodiment 3:
[0104] The difference between this comparative example and Example 1 is that the additive type and additive concentration in the copper foil electrochemical deposition process are adjusted: the collagen (Mw 2500-3500 g / mol) with a concentration of 5 mg / L in the electrolyte is replaced with choline chloride with a concentration of 15 mg / L.
[0105] Embodiment 4:
[0106] The difference between this comparative example and Example 1 is that the additive type and additive concentration in the copper foil electrochemical deposition process are adjusted: the collagen (Mw 2500-3500 g / mol) with a concentration of 5 mg / L in the electrolyte is replaced with gelatin with a concentration of 10 mg / L.
[0107] Embodiment 5:
[0108] The difference between this comparative example and Example 1 is that the current density and the cathode roller linear speed during the copper foil electrochemical deposition process were adjusted: (1) the current density was adjusted from 10 kA / m2 to 12 kA / m 2 ; (2) The cathode roller linear speed was adjusted from 5 m / min to 8 m / min.
[0109] Embodiment 6:
[0110] The difference between this comparative example and Example 1 is that (1) the components and concentrations in the anti-oxidation treatment are adjusted: the concentration of graphene oxide GO in the anti-oxidation electrolyte is adjusted from 0.5 g / L to pyrrole Py with a concentration of 1.0 g / L; (2) the parameters of the pulse circuit during the anti-oxidation treatment are adjusted: the average current density is increased from 10 A / m 2 Adjust to 5A / m 2 , the duty cycle is adjusted from 33% to 25%, and the frequency is adjusted from 1000Hz to 100Hz.
[0111] Embodiment 7:
[0112] The difference between this comparative example and Example 1 is that (1) the components and concentrations in the anti-oxidation treatment are adjusted: the concentration of graphene oxide GO in the anti-oxidation electrolyte is adjusted from 0.5 g / L to aniline ANI with a concentration of 1.5 g / L; (2) the parameters of the pulse circuit during the anti-oxidation treatment are adjusted: the average current density is increased from 10 A / m 2 Adjusted to 15A / m 2 , the duty cycle is adjusted from 33% to 67%, and the frequency is adjusted from 1000Hz to 2000Hz.
[0113] Embodiment 8:
[0114] The difference between this comparative example and Example 1 is that (1) the components and concentrations in the anti-oxidation treatment are adjusted: the concentration of graphene oxide GO in the anti-oxidation electrolyte is adjusted from 0.5 g / L to phytic acid PA with a concentration of 1.0 g / L; (2) the parameters of the pulse circuit during the anti-oxidation treatment are adjusted: the average current density is increased from 10 A / m 2 Adjusted to 5A / m 2 , the duty cycle is adjusted from 33% to 25%, and the frequency is adjusted from 1000Hz to 2000Hz.
[0115] Embodiment 9:
[0116] The difference between this comparative example and Example 1 is that (1) the components and concentrations in the anti-oxidation treatment are adjusted: the concentration of graphene oxide GO in the anti-oxidation electrolyte is adjusted from 0.5 g / L to benzotriazole BTA at a concentration of 1.5 g / L; (2) the parameters of the pulse circuit during the anti-oxidation treatment are adjusted: the average current density is increased from 10 A / m 2 Adjusted to 15A / m 2 , the duty cycle is adjusted from 33% to 67%, and the frequency is adjusted from 1000Hz to 100Hz.
[0117] Embodiment 10:
[0118] The difference between this comparative example and Example 1 is that (1) the components and concentrations in the anti-oxidation treatment are adjusted: the concentration of graphene oxide GO in the anti-oxidation electrolyte is adjusted from 0.5 g / L to 1.0 g / L of KH792 silane coupling agent; (2) the parameters of the pulse circuit during the anti-oxidation treatment are adjusted: the average current density is increased from 10 A / m 2 Adjusted to 15A / m 2 , the duty cycle is adjusted from 33% to 25%, and the frequency is adjusted from 1000Hz to 2000Hz.
[0119] Embodiment 11:
[0120] The difference between this comparative example and Example 1 is that (1) the components and concentrations in the anti-oxidation treatment are adjusted: the concentration of graphene oxide GO in the anti-oxidation electrolyte is adjusted from 0.5 g / L to zinc sulfate ZnSO4 with a concentration of 1.0 g / L; (2) the parameters of the pulse circuit during the anti-oxidation treatment are adjusted: the average current density is increased from 10 A / m 2 Adjusted to 15A / m 2 , the duty cycle is adjusted from 33% to 25%, and the frequency is adjusted from 1000Hz to 200Hz.
[0121] Comparative Example 1
[0122] The difference between this comparative example and Example 1 is that no additive is introduced during the electrochemical deposition of copper ions, and electrochemical deposition is directly performed using CuSO4 and H2SO4 as electrolyte. The parameters during the electrochemical deposition are as follows:
[0123] Cu 2+ Concentration: 80g / L
[0124] H2SO4 concentration: 200g / L
[0125] Electrolyte temperature: 55°C
[0126] Electrolyte flow rate: 40m 3 / h
[0127] Current density: 80A / dm 2
[0128] Cathode roller linear speed: 5.0m / min
[0129] Comparative Example 2:
[0130] The difference between this comparative example and Example 1 is that an electrolyte containing chromium Cr(VI) is used for anti-oxidation treatment during the anti-oxidation process. The specific parameters in the electrochemical deposition process of the Cr-containing passivation layer are as follows:
[0131] Cr(VI) concentration: 1.0g / L
[0132] Glucose concentration: 5g / L
[0133] pH: 3.5
[0134] Current density: 10A / dm 2
[0135] Current mode: DC
[0136] In order to more intuitively reflect the implementation effect of the present invention, the microscopic morphology and parameters of the samples produced in the embodiment were analyzed and characterized by means of field emission-scanning electron microscope (FE-SEM Zeiss, Sigma300), scanning electron microscope (TESCAN, VEGA3) and laser confocal microscope (Olympus, OLS5100).
[0137] like Figure 4 The cross-sectional SEM image of the double-sided roughened copper foil produced in Example 1 is shown. From the image, it can be observed that the upper and lower surfaces of the copper foil both present obvious undulating mountain-shaped contours, and there are obvious valley areas between adjacent peaks. The thickness of the copper foil is about 8.0 μm. The upper and lower surfaces of the copper foil are further observed by scanning electron microscopy. Figure 5As shown in the figure, irregular peak-like microstructures with ups and downs can be clearly observed on the upper and lower surfaces of the copper foil. The bottom size of the peak does not exceed 5.0μm, which is consistent with the Figure 4 The formation of micron-scale peaks can effectively increase the contact area between the copper foil current collector and the lithium metal negative electrode, which is beneficial to improve the current transmission efficiency. On the other hand, it can induce the orderly deposition of lithium metal and reduce the risk of disordered growth of lithium dendrites causing the separator to pierce the battery short circuit. In addition, compared Figure 5 (a) and Figure 5 (b) It can be found that there is no obvious difference in the microscopic morphology of the upper and lower surfaces of the copper foil. The consistency of the morphology of the upper and lower surfaces of the copper foil is closely related to the use of the same electrolyte composition in the S01 and S02 treatment processes. Figure 6 The surface profile cloud map obtained by using a laser confocal microscope to measure the surface profile of the sample in Example 1 is shown. The green area with relatively high roughness corresponds to the peak area on the SEM image, and the blue area with relatively low roughness corresponds to the valley area in the SEM image. Figure 6 (a) and Figure 6 (b) It can be found that the observed area is mainly green and there is no red area, indicating that the roughness of the sample is relatively low.
[0138] The following table is a parameter table of each copper foil product in the embodiments and comparative examples; the key technical indicators of the embodiments and comparative examples under different parameter conditions are listed. It can be found from the table that the double-sided roughened electrolytic copper foil generated by the embodiment of the present invention has a lower roughness, and the difference in contour between the upper and lower surfaces is small, and the color difference between the upper and lower surfaces is relatively small. In comparative example 1, no additives were introduced during the production process. The surface roughness Rz of the copper foil was relatively large, and there were significant differences in the roughness and color difference between the upper and lower surfaces. Therefore, the selection of suitable additives can play a positive role in reducing the surface contour of the copper foil and reducing the color difference of the copper foil surface. The smaller the difference in the roughness of the upper and lower surfaces of the copper foil, the smaller the impedance difference between the current collector and the electrode. The reduction of the difference in interface impedance plays a vital role in improving the cycle stability and safety of lithium metal batteries.
[0139]
[0140]
[0141] Finally, it should be noted that the above description is only a preferred example of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for producing a double-sided roughened copper foil, characterized in that: The following steps are involved: S1. Electrochemically depositing a single-sided roughened copper foil using additives. By introducing additives, the electrochemical deposition process of copper ions is regulated to form a single-sided roughened electrolytic copper foil with one side being flat and the other side having undulating peaks. S2, electrochemically depositing a roughened structure on the smooth surface of the single-sided roughened copper foil; forming a roughened structure with undulating peaks on the smooth surface of the single-sided smooth copper foil through an additive-assisted electrochemical deposition process, thereby forming a double-sided roughened electrolytic copper foil; S3, performing anti-oxidation treatment on both sides of the double-sided roughened copper foil; Using chromium-free passivation technology, an oxide layer is deposited on the upper and lower surfaces of the double-sided roughened copper foil by pulse electrochemical deposition; S4, drying the double-sided roughened copper foil; removing the residual moisture on the surface of the copper foil by passing the double-sided anti-oxidation treated copper foil through a blast oven; S5. Finally, the double-sided roughened electrolytic copper foil is rolled up; The double-sided roughened copper foil that has completed double-sided anti-oxidation treatment is collected into a roll under a certain tension by a winding device.
2. The method for producing a double-sided roughened copper foil according to claim 1, characterized in that: The same electrolyte is used in the electrochemical deposition of single-sided copper foil and the roughening of the surface. The main components of the electrolyte include CuSO4, H2SO4, Cl - and leveling agents.
3. The method for producing a double-sided roughened copper foil according to claim 2, characterized in that: The leveling agent in the electrolysis and roughening electrolyte includes one or more of hydroxyethyl cellulose HEC, choline chloride, gelatin, and collagen, wherein the concentration of the leveling agent is between 5-20 mg / L.
4. The method for producing a double-sided roughened copper foil according to claim 1, characterized in that: The thickness of the double-sided roughened copper foil is between 6 and 10 μm, the roughness difference ΔRz between the two sides of the double-sided roughened copper foil is less than or equal to 1.0 μm, and the color difference ΔE between the upper and lower sides of the double-sided roughened copper foil is less than or equal to 2.
0.
5. The method for producing a double-sided roughened copper foil according to claim 1, characterized in that: The anti-oxidation treatment liquid used for chromium-free passivation includes one or more of phytic acid, benzotriazole, KH792 silane coupling agent, graphene oxide, pyrrole, aniline, and zinc sulfate, wherein the concentration of the anti-oxidation treatment liquid is between 0.5-1.5 g / L.
6. The method for producing a double-sided roughened copper foil according to claim 1, characterized in that: The average current density during the pulse electrochemical deposition of the double-sided roughened copper foil anti-oxidation layer is 5-15A / m 2 The duty cycle is between 25-67% and the frequency is between 100-2000Hz.
7. A double-sided roughened copper foil, characterized in that: The double-sided roughened copper foil is prepared according to the production method of the double-sided roughened copper foil according to any one of claims 1 to 6.
8. The double-sided roughened copper foil according to claim 7, characterized in that: The finished double-sided roughened copper foil has undulating mountain-like microstructures on both sides, and the roughness Rz of the upper and lower surfaces is between 1.5-3.0μm.
9. A production equipment for double-sided roughened copper foil, characterized in that: Includes the following equipment: 1) Single-sided roughened copper foil electrochemical deposition device; 2) Electrochemical deposition device for roughening the surface; 3) Double-sided anti-oxidation electrochemical deposition device; 4) Blast drying device; 5) Double-sided roughened electrolytic copper foil winding device.
10. The production equipment of double-sided roughened copper foil according to claim 1, characterized in that: An auxiliary cathode is provided in the anti-oxidation treatment tank in the double-sided anti-oxidation electrochemical deposition device to remove the copper ions brought into the copper foil surface from the treatment solution to ensure the effectiveness of the anti-oxidation treatment. The auxiliary cathode is made of copper rod and the current is between 5-15A.